Selective excitation of LG 00, LG 01, and LG 02 modes by a solid core PCF based mode selector in MDM-Ro-FSO transmission systems. (25th May 2018) - Chaudhary, Sushank; Amphawan, Angela
Abstract: Radio over free space (Ro-FSO) provides an ambitious platform for seamless integration of radio networks to optical networks. Three independent channels, each carrying 2.5 Gbps–5 GHz data, are successfully transmitted over a free space link of 2.5 km by using mode division multiplexing (MDM) of three modes LG 00, LG 01, and LG 02 modes in conjunction with solid core photonic crystal fibers (SC-PCFs). Moreover, SC-PCFs are used as a mode selector in the proposed MDM-Ro-FSO system. The results are reported in terms of bit error rate, mode spectrum, and spatial profiles. The performance of the proposed Ro-FSO system is also evaluated under the influence of atmospheric turbulence in the form of different levels of fog, namely, light fog, thin fog, and heavy fog.